2019
DOI: 10.1016/j.jebo.2019.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Was Brexit triggered by the old and unhappy? Or by financial feelings?

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 34 publications
(32 reference statements)
5
44
0
Order By: Relevance
“…Inequality, and especially perceived inequality, has been documented by Liberini, Oswald, Proto, and Redoano (2019) as a trigger for the Brexit vote. They illustrate the importance of perceived relative deprivation (as compared to the actual financial state of the individual) as a factor for voting for the Leave campaign in the Brexit referendum.…”
Section: “Voting With Their Feet” and Other Brexit Hypothesesmentioning
confidence: 99%
“…Inequality, and especially perceived inequality, has been documented by Liberini, Oswald, Proto, and Redoano (2019) as a trigger for the Brexit vote. They illustrate the importance of perceived relative deprivation (as compared to the actual financial state of the individual) as a factor for voting for the Leave campaign in the Brexit referendum.…”
Section: “Voting With Their Feet” and Other Brexit Hypothesesmentioning
confidence: 99%
“…Our results for the socio-demographic controls (the propensity to vote leave is lower for women, those with university degrees and of Scottish or European ancestry) are in line with the profile of the Brexit voter: old white man, English, and low educated (Ashcroft, 2016;Goodwin & Heath, 2016;Swales, 2016). The lack of significance of the socio-economic controls is interesting, given that the austerity policies after the 2008 financial crisis have been blamed for the leave outcome (Dorling, 2016) and Brexiteers have been depicted as financially concerned (Liberini et al, 2019), economically deprived (Swales, 2016), and losers of globalisation (Hobolt, 2016). Finally, the positive relationship between general satisfaction and the leave vote goes in line with Janmaat et al (2018), for whom the only group showing a significant increase in support for the Brexit was "the highly engaged and satisfied", which expressed satisfaction with democracy and high levels of trust in public officials; and with Liberini et al (2019), who found that the completely satisfied people were fractionally more likely to vote leave than the mostly dissatisfied ones.…”
Section: Resultsmentioning
confidence: 99%
“…Not only had the NHS pledge a great impact on the British public but the leave campaign was described, overall, as more consistent because it confined itself to a small set of topics and core values (Shaw, Smith & Scully, 2017). Its success might have translated in two facts: the pro Brexit percentage increased as the deadline vote day became closer (Liberini, Oswald, Proto & Redoano, 2019), and the only type of voter profile, which was also the most numerous (30.3 per cent), recording a significant increase in support for leave from 2016 to 2017 was the highly politically engaged, which was also the more susceptible to the leave campaign (Janmaat, Melis, Green & Pensiero, 2018).…”
Section: Political Turmoil and The Brexitmentioning
confidence: 99%
“…While recent psychological research has studied voter preferences in the context of Brexit (Harper & Hogue, 2019;Liberini, Oswald, Proto, & Redoano, 2019;Macdougall, Feddes, & Doosje, 2020), the human consequences of the referendum remain largely understudied (Brophy, 2019) -especially in populations of British citizens living within the EU. This research explored the lived experiences of Brexit for British Remain-Minded citizens living in Luxembourg.…”
Section: Discussionmentioning
confidence: 99%